Teaching Business Discourse - Ilie, Cornelia; Nickerson, Catherine; Planken, Brigitte (Research and Practice in Applied Linguistics, 2019)
This book presents research in business discourse and offers pedagogical approaches to teaching business discourse in both classroom and consultancy contexts that address the key issues of dealing with different types of learners, developing teaching materials and evaluation. Drawing on the authors' extensive experience of researching business discourse from a variety of different perspectives including pragmatics, discourse analysis, rhetoric, and language for specific purposes, it demonstrates how these approaches may be applied to teaching. Each chapter includes a list of additional readings, together with a number of practical tasks designed to help readers apply the materials presented. Case studies are used throughout the book to illustrate the concepts, thus equipping readers with a set of research tools to extend their own understanding of how language and communication operate in business contexts, as well introducing them to a variety of research-based ideas that can be translated easily into a classroom setting. The book is cross-cultural in scope as it includes perspectives from a range of different contexts. It represents a significant advance in current literature and will provide a valuable resource for students and scholars of applied linguistics, business communication, and business discourse, in addition to teachers of Business English. Cornelia Ilie is Professor of Linguistics and Rhetoric, Strömstad Academy, Sweden. Catherine Nickerson is Professor of Business Communication at Zayed University, United Arab Emirates. Brigitte Planken is Associate Professor of Communication and Information Studies, Radboud University, the Netherlands.